2011
DOI: 10.1007/s11064-011-0564-5
|View full text |Cite
|
Sign up to set email alerts
|

[+]-Huperzine A Protects Against Soman Toxicity in Guinea Pigs

Abstract: The chemical warfare nerve agent (CWNA) soman irreversibly inhibits acetylcholinesterase (AChE) causing seizure, neuropathology and neurobehavioral deficits. Pyridostigmine bromide (PB), the currently approved pretreatment for soman, is a reversible AChE inhibitor that does not cross the blood-brain barrier (BBB) to protect against central nervous system damage. [-]-Huperzine A, a natural reversible AChE inhibitor, rapidly passes through the BBB and has numerous neuroprotective properties that are beneficial f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Decreased peripheral input induced by auditory trauma and aging leads to altered cortical activity patterns, including increased spontaneous firing rates, synchronized epileptic-like neuronal activity, and basal excitatory postsynaptic potentials (for a review, see Knipper et al, 2013 ). Plastic tinnitus-related changes include loss of glycinergic inhibition in the adult dorsal cochlear nucleus and/or loss of GABAergic inhibition in the inferior colliculus and higher centers, resulting in aberrant cortical activity patterns (Wang et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Decreased peripheral input induced by auditory trauma and aging leads to altered cortical activity patterns, including increased spontaneous firing rates, synchronized epileptic-like neuronal activity, and basal excitatory postsynaptic potentials (for a review, see Knipper et al, 2013 ). Plastic tinnitus-related changes include loss of glycinergic inhibition in the adult dorsal cochlear nucleus and/or loss of GABAergic inhibition in the inferior colliculus and higher centers, resulting in aberrant cortical activity patterns (Wang et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that certain reversible AChE inhibitors can be used for pre‐exposure treatment of OP poisoning (for a critical review see 33 ). In particular, huperzine A, administered 30 min before OP challenge, protects against 1.2 × LD 50 soman in guinea pigs 48 and administered up to 6 h before exposure, protects mice against 2.2 × LD 50 soman 49 . However, there is no information that huperzine A can protect after significantly longer than 6 h period of pretreatment.…”
Section: Discussionmentioning
confidence: 99%
“…Just as is the case with pyridostigmine, due to the presence of a positive charge on the quaternary nitrogen, C547 is poorly able to penetrate the blood–brain barrier. However, it is well known that acute OP poisoning leads to death mainly due to respiratory failure caused by central apnea resulting from depression of the respiratory center and peripheral cholinergic effects, such as bronchospasm, and respiratory muscle failure 48 . The exact balance between central and peripheral mechanisms in causing death is complex and strongly dependent both on animal species and chemical nature of the OP agent.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, studies have demonstrated that piperine holds a moderate to good BBB permeability (Eigenmann et al, 2016; Ren & Zuo, 2019). Huperzine A , a sesquiterpene alkaloid derived from Huperzia serrata is reported to possess a good ability to cross BBB (Ying Wang et al, 2011; Chen, Cheng, et al, 2019), however, due to low aqueous solubility, poor bioavailability and toxicity upon larger intake the therapeutic efficacy of huperzine A faces limitation (Chen, Cheng, et al, 2019; Li et al, 2017). Huperzine A is known for its neuro‐enhancing effects in AD (Friedli & Inestrosa, 2021).…”
Section: Phyto‐compounds and Their Neuroprotective Effects In Ad And ...mentioning
confidence: 99%